De-novo Histoid Hansen’s Disease: Case Report with short Review of Literature: De-novo Histoid Hansen’s Disease: Case Report with short Review of Literature - Awake, Praneet P.; Bhosale, Anand; Bindu, Rajan (Journal of Pakistan Association of Dermatologists, 2022)
Histoid Hansen’s disease is a rare form of multibacillary leprosy. It has characteristic clinical and histopathological features. It is considered to be a form of lepromatous leprosy. It can arise in lepromatous patients with inadequate or irregular treatment, who relapse after dapsone monotherapy due to dapsone resistance or may rarely occur ‘de-novo’. It may present as diagnostic enigma to the physicians. We present a case of de-novo histoid leprosy in a 20-year-old female.